Urosepsis in Geriatric Patients Urosepsis beim geriatrischen Patienten - Yapan, F.; Wiedemann, A.; Heppner, Hans Jürgen (Aktuelle Urologie, 2016)
Due to the demographic shift, increasing numbers of geriatric patients are admitted to acute care hospitals of all levels of care. This means that special challenges must be met in the medical care and management of these patients. Immunosenescence and multimorbidity make elderly patients vulnerable to infectious diseases. Urinary tract infections range from "simple" cystitis to pyelonephritis and urosepsis and, at 25%, are the second most common form of infection in geriatric patients. It is often difficult to make a diagnosis because typical symptoms do not always occur. Urosepsis, a hyperactive and uncontrolled immune response of the organism due to exogenous damage, is based on bacterial infection of the urogenital tract. Urinary retention, immunosuppressive medication, malignancy, diabetes mellitus and renal or prostatic processes promote the risk for urosepsis. Complicated urosepsis additionally comprises a structural or functional abnormality, including ureteral obstruction. Risk factors for urosepsis are urinary incontinence, an indwelling urinary catheter, hydronephrosis or ureteral calculi. Patients suffering from diabetes mellitus are also at a higher risk for urosepsis. When diagnosing elderly patients, one has to consider that the classic symptoms can be masked by multimorbidity, or septic encephalopathy and acute confusion (delirium) may be the only symptoms. Body temperature is lower in elderly patients and does not necessarily rise to 38 °C or more in the acute phase. In patients older than 75 years who are suspicious for sepsis, temperatures as low as 37.4 °C should be rated as fever. Treatment of urosepsis basically includes clearing the focus, antimicrobial treatment, stabilisation of circulation and replacement of failed organ functions. Initial empiric antibiotic treatment, depending on local resistance, should be done with acylaminopenicilline and beta-lactamase inhibitors (e.g. piperacillin/combactam or tazobactam or group 3 cephalosporins (e.g. cefotaxim). In case of intolerance, fluoroquinolone with high urinary excretion or carbapenem can be used. Also multidrug resistant germs are of importance for urosepsis and require appropriate initial antibiotic treatment. The multimorbidity of geriatric patients puts them at risk for a severe course of infectious diseases. Early identification of high-risk patients and geriatric expert monitoring in intensive care units may assist intensive care physicians. Treatment success in intensive care can be maintained by early geriatric acute rehabilitation. This requires all those involved to enter into an interdisciplinary and interprofessional dialogue.
CRIS-Team Scopus Importer:2022-09-26
Keywords: fever; geriatric patients; sepsis; SIRS; urosepsis